Long-Term Exposures to Air Pollutants and Risk of Peripheral Arterial Occlusive Disease: A Nationwide Cohort Study in Taiwan - Liao, Shu-Hui; Chiu, Chien-Shan; Jang, Li-Ho; Hu, Sung-Yuan; How, Chorng-Kuang; Hsieh, Vivian Chia-Rong; Hsieh, Ming-Shun (Frontiers in Cardiovascular Medicine, 2022)
Air pollution is one of the most alarming environmental issues that causes multiple health hazards. An association between air pollution and cardiovascular diseases has been established through many prior studies. In this study, we aimed to evaluate the risk of long-term exposure to air pollution (PM2.5, CO and NO2) and its association with the risk of developing peripheral arterial occlusive disease (PAOD). PAOD is a condition involving impairment of perfusion of blood in the distal parts of the aorta due to narrowing of the arteries (arterial stenosis) and has been reported as a risk factor for developing cardiovascular diseases. Furthermore, risk of PAOD increases with age, and hence is a serious public health issue and a cause for concern, especially for an aging society such as Taiwan. Two national-scale databases from Taiwan, the national health insurance database (NHIRD) and the Taiwan air quality-monitoring database (TAQMD) were linked to conduct this cohort study between 2003 and 2013. Cox proportional hazards regression with time-dependent modeling was used to evaluate the hazard ratio (HR) for PAOD with respect to daily exposure to air pollutants. The concentrations of each of the pollutants of interest (PM2.5, NO2 and CO) were categorized into four categories according to the daily average concentration of air pollutants for every quarter of the year, Q1 to Q4 (Q4 = highest). The cumulative incidence of PAOD was examined by Kaplan-Meier analysis with two-tailed log-rank test. A total of 1,598 PAOD cases were identified during the 10-year follow-up period, along with 98,540 non-PAOD controls. In the multivariate analysis, after adjusting for age, gender, urbanization level, residential area, baseline comorbidities, and medications, the adjusted HRs were PM2.5 = 1.14 (95% CI 1.13-1.16), NO2 = 1.03 (95% CI 1.02-1.04), and CO = 2.35 (95% CI 1.95-2.84). Kaplan-Meier analysis showed that CO (P <0.0001) and PM2.5 (P <0.0001) concentrations were strongly and positively associated with the cumulative incidence of PAOD during the follow-up period. Findings from this study established that prolonged exposure to air pollutants CO and PM2.5 are significant factors that, among other well-known causes, may also play a potential role in PAOD pathogenesis.